2019
DOI: 10.1021/acs.organomet.8b00700
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Activity of Iron Hydride Ligated with Bidentate N-Heterocyclic Silylenes for Hydroboration of Carbonyl Compounds

Abstract: We report the synthesis of a novel bidentate Nheterocyclic silylene (NHSi) ligand, N-(LSi:)-N-methyl-2-pyridinamine (1) (L = PhC(NtBu) 2 ), and the first bischelate disilylene iron hydride, [(Si,N)(Si,C)Fe(H)(PMe 3 )] (2), and monosilylene iron hydride, [(Si,C)Fe(H)(PMe 3 ) 3 ] (2′), through C sp 2 −H activation of the NHSi ligand. Compounds 1 and 2 were fully characterized by spectroscopic methods and single-crystal X-ray diffraction analysis. Density functional theory calculations indicated the multiple-bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 72 publications
3
66
0
Order By: Relevance
“…The Yb atom in complex 3 is in a distorted square pyramidal geometry (τ<0.13), [20] chelated by a newly formed anionic silylene‐pyridyl‐amido ligand ([SiNN]). Only a few examples of multidentate anionic silylene ligands have been reported in the last 10 years, most of them being accessed by intramolecular C−H or Si−H bond activation when using low‐valent transition metal precursors [2c, 3d, 4k, 21] . The distance between the Yb atom and the pyridine nitrogen atom in 3 (2.314(4) Å) is slightly longer than the distance with the amide nitrogen donor (2.256(4) Å), suggesting that the anionic charge is localized at the amide N‐atom and supporting an amidopyridine (rather than aminopyridinato) [22] coordination mode of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…The Yb atom in complex 3 is in a distorted square pyramidal geometry (τ<0.13), [20] chelated by a newly formed anionic silylene‐pyridyl‐amido ligand ([SiNN]). Only a few examples of multidentate anionic silylene ligands have been reported in the last 10 years, most of them being accessed by intramolecular C−H or Si−H bond activation when using low‐valent transition metal precursors [2c, 3d, 4k, 21] . The distance between the Yb atom and the pyridine nitrogen atom in 3 (2.314(4) Å) is slightly longer than the distance with the amide nitrogen donor (2.256(4) Å), suggesting that the anionic charge is localized at the amide N‐atom and supporting an amidopyridine (rather than aminopyridinato) [22] coordination mode of the ligand.…”
Section: Resultsmentioning
confidence: 99%
“…[9] We synthesized silylene iron hydride by activating the C (sp 2 )-H bond on the pyridine ring to catalyze hydroboration of carbonyl compounds under mild conditions. [15] Recently, we reported a bis-silylene iron hydride obtained by activation of C (sp 3 )-H bond. [16] It was proved that this iron hydride could effectively catalyze nitrogen reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal (M) complexes containing HT ligands have been known for more than 40 years, however, the investigation of their applicability in the field of homogeneous catalysis is as yet in its initial stages,[2a], particularly in comparison with that of NHC complexes . Such a dissimilar situation is mainly a consequence of the generally lower stability of HT‐M complexes, since degradation reactions involving oxidation, hydrolysis and substitution processes are well known for systems of this kind.…”
Section: Introductionmentioning
confidence: 99%
“…Such a dissimilar situation is mainly a consequence of the generally lower stability of HT‐M complexes, since degradation reactions involving oxidation, hydrolysis and substitution processes are well known for systems of this kind. However, the last few years have witnessed the appearance of a family of bi‐ and tridentate ligands containing one or more HTs as donor groups that not only present significant catalytic activities in a number of organic transformations but have also shown that the HT groups play a steering role in the catalytic reactions. [2a] Figure presents the bi‐ ( I – IX ) and tridentate ( X – XI ) HT ligands whose transition metal complexes (or at least some of them) have already proven to be active catalysts (or catalyst precursors) in homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%